IDENTIFICATION OF NOVEL HIGH-AFFINITY CYTOPLASMIC ASPARAGINYL-TRNA SYNTHETASE INHIBITORS USING DOCKING AND MOLECULAR SIMULATION - Singh, Rahul; Shirazi, Tazmeen (Asian Journal of Pharmaceutical and Clinical Research, 2015)
ABSTRACT Lymphatic filariasis is an endemic disease affecting humans in more than 83 countries, and it is crucial to find drugs to cure this disease. Nearly 1.33 billion were at risk of filariasis. In this study, we have targeted Brugia malayi asparaginyl tRNA synthetase (AsnRS) for new drug development against filariasis. AsnRS is an essential enzyme for protein synthesis in nematodes and required at various steps of their life cycle. We used computational tools for identifying potential molecule which can act as an inhibitor for our target AsnRS. 4133 molecules were selected after screening using Zinc Pharmer and were docked in high throughput manner using vina and top 10% highest scoring molecules were selected. These molecules were re-docked, and only those molecules were selected which shows less than 2Ã… root-mean-square deviation difference in the top pose predicted by both Autodock4 and Autodock Vina. We identified 11 molecules fitting these criteria which were further subjected to interaction analysis. Molecular dynamics simulations were performed on molecules showing best interaction based on their binding energy and hydrogen bond formation. It was seen that these molecules were bound tightly inside the active site of the receptor. These molecules seem a suitable candidate to undergo in vitro testing. Keywords: Docking, Filariasis, Virtual screening, asparaginyl tRNA synthetase.